2020
DOI: 10.1002/anie.202005883
|View full text |Cite
|
Sign up to set email alerts
|

On the Promotion of Catalytic Reactions by Surface Acoustic Waves

Abstract: Surface acoustic waves (SAW) allow to manipulate surfaces with potential applications in catalysis,s ensor and nanotechnology.SAWswere shown to cause astrong increase in catalytic activity and selectivity in many oxidation and decomposition reactions on metallic and oxidic catalysts. However,t he promotion mechanism has not been unambiguously identified. Using stroboscopic X-ray photoelectron spectro-microscopy, we were able to evidence as ub-nanosecond work function change during propagation of 500 MHz SAWs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Thus, up to 6-fold rate enhancement has been reported for the catalytic oxidation of CO over platinum films using SAWs under high vacuum . Although various hypotheses have been suggested, both photoelectron microscopy and dynamic simulations support the thermal activation resulting from energy dissipation along with reversible surface deformation . The latter can enhance catalytic rates via sorption–desorption process induced by the acoustic oscillations.…”
Section: Flow and Automation: The Present And Futurementioning
confidence: 99%
“…Thus, up to 6-fold rate enhancement has been reported for the catalytic oxidation of CO over platinum films using SAWs under high vacuum . Although various hypotheses have been suggested, both photoelectron microscopy and dynamic simulations support the thermal activation resulting from energy dissipation along with reversible surface deformation . The latter can enhance catalytic rates via sorption–desorption process induced by the acoustic oscillations.…”
Section: Flow and Automation: The Present And Futurementioning
confidence: 99%
“…Through long-term practice and training to develop functional body movement of the “screening” method and the basic action, the body's basic action with sports anatomy, sports biomechanics, sports physiology, and neuroscience are integrated together, through the comprehensive analysis and functional activities of final screening of action, the action is easy to operate, and the equipment requirements are not high. The stability and controllability of each action are strong, and the evaluation method is simple [ 4 ]. A comprehensive evaluation of the posture and form of the body when doing the movements such as static, dynamic, and rotating was made.…”
Section: Introductionmentioning
confidence: 99%
“…While the electronic degrees of freedom of both the reagent and substrate are central to understanding the binding free-energy, and thus reactivity per Sabatier's principle, 1,2 recent experiments and theoretical studies have highlighted the often underappreciated role of substrate vibrations in modulating the reaction dynamics at metal interfaces. [3][4][5][6][7][8][9][10][11][12] For example, several studies have shown that laser pulses can be used to indirectly excite surface phonons and subsequently increase desorption rates and reactivity. [3][4][5][6]13 It has been shown that applying acoustic waves to a catalyst surface at an appropriate polarization and resonant frequency, can also greatly increase reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6]13 It has been shown that applying acoustic waves to a catalyst surface at an appropriate polarization and resonant frequency, can also greatly increase reactivity. 7,12,14 It is not clear whether such enhancements of reactivity are due to an effective reduction of the binding energy, or due to kinetic factors which go beyond Sabatier's purely thermodynamic principle. In light of such experiments, an improved understanding of the ways in which substrate vibrations may modulate reactivity is greatly desired.…”
Section: Introductionmentioning
confidence: 99%